Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1186/s12863-022-01040-2
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 and human retroelements: a case for molecular mimicry?

Abstract: Background The factors driving the late phase of COVID-19 are still poorly understood. However, autoimmunity is an evolving theme in COVID-19’s pathogenesis. Additionally, deregulation of human retroelements (RE) is found in many viral infections, and has also been reported in COVID-19. Results Unexpectedly, coronaviruses (CoV) – including SARS-CoV-2 – harbour many RE-identical sequences (up to 35 base pairs), and some of these sequences are part o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 101 publications
0
4
0
Order By: Relevance
“…A foreign-derived antigen activates autoreactive T and B cells in a vulnerable individual when peptides derived from foreign and self-peptides have similarities. Additional links to our understanding of molecular mimicry include host genetics, microbiota exposure, and environmental chemicals [34] .Molecular mimicry has been proposed as a cause of the autoimmune phenomena observed in COVID-19 [35] , [36] .As a result of analyzing tissues from COVID-19 victims, they identified cellular and molecular patterns that lead to the damage of epithelial and other structures resulting in death, which underscores the role of autoimmunity brought on by molecular mimicry in the pathology of COVID-19 [37] . Another study supported this idea, that self-reactivity against proteins involved in activation/development of B- and T-cells can be explained by molecular mimicry.…”
Section: A Major Mechanism For Triggering An Autoimmune Reaction By S...mentioning
confidence: 99%
“…A foreign-derived antigen activates autoreactive T and B cells in a vulnerable individual when peptides derived from foreign and self-peptides have similarities. Additional links to our understanding of molecular mimicry include host genetics, microbiota exposure, and environmental chemicals [34] .Molecular mimicry has been proposed as a cause of the autoimmune phenomena observed in COVID-19 [35] , [36] .As a result of analyzing tissues from COVID-19 victims, they identified cellular and molecular patterns that lead to the damage of epithelial and other structures resulting in death, which underscores the role of autoimmunity brought on by molecular mimicry in the pathology of COVID-19 [37] . Another study supported this idea, that self-reactivity against proteins involved in activation/development of B- and T-cells can be explained by molecular mimicry.…”
Section: A Major Mechanism For Triggering An Autoimmune Reaction By S...mentioning
confidence: 99%
“…For example, KRT19 and FOXL2 were expressed in female somatic cells to discriminate pre-granulosa cells, 24 while SOX9 and DMRT1 guide common progenitors to early male somatic lineages 24 , 25 ( Figures S2 B and S2C; Table S2 ). Despite the potential fusion of SARS-CoV-2 RNA with retrotransposon-identical transcripts, especially long interspersed nuclear elements (LINEs) and short interspersed nuclear elements (SINEs), 26 , 27 we did not detect a prominent change in the expression of transposable elements (TEs) in FGCs between the exposed group and the uninfected group ( Figure 2 C). Meanwhile, we identified only 43 and 30 significantly differentially expressed genes (DEGs) in male and female FGCs, respectively, upon maternal exposure to SARS-CoV-2 ( Figures 2 D and 2E; Table S3 ).…”
Section: Resultsmentioning
confidence: 92%
“…Expression of retrotransposons is deregulated in many viral infections, including in COVID-19 patients. For example, LINE-1 ORF1p and ORF2p proteins have peptides identical to the SARS-CoV-2 epitope, which are targeted by Abs in COVID-19 and thus could induce an autoimmune loop by molecular mimicry with build-up of autoreactive CD4+ Th cells [ 18 ]. Another hypothesis is that coronavirus infection may increase retrotransposon expression through enhancing global demethylation activity [ 21 ].…”
Section: The Influence Of Retrotransposons On Diseasesmentioning
confidence: 99%
“…An EVE is a DNA sequence derived from a virus, and present within the germline of a non-viral organism [ 15 ]. They have been shown to be important players in genome stability and can provoke genomic rearrangements, some of which have already been associated with various diseases and pathological conditions, such as cancer, neurodegenerative diseases, autoimmunity, viral infections, and inflammation [ 16 , 17 , 18 , 19 ]. In T1D, they may represent the missing link between genetic susceptibility and environmental factors ( Figure 1 ), because it has been shown that viruses can activate the expression of some EVE families [ 20 ], and this phenomenon has also been proposed for coronavirus [ 21 ].…”
Section: Introductionmentioning
confidence: 99%